Oncofertility in sarcoma patients - Lopategui, Diana M.; Yechieli, Raphael; Ramasamy, Ranjith (Translational Andrology and Urology; Vol 6, No 5 (October 26, 2017): Translational Andrology and Urology (Management of Penile Cancer), 2017)
Treatment for sarcoma can significantly decrease fertility, both due to the irradiation of gonads, and the impact of chemotherapy on gametogenesis. Infertility in cancer survivors causes significant regret and decreased quality of life in their adulthood. As this cancer mainly affects children and young adults, fertility preservation is an essential part of survivorship care, however it remains one of the least implemented services in adolescent and young adult cancer patients. Success of fertility preservation is highly dependent on the referral prior to oncologic treatment. Early patient counseling with possible consult with oncofertility specialists should be offered to every oncologic patient in reproductive age or younger. There are several options available and in continuous evolution for fertility preservation. Cryopreservation of sperm and oocytes constitutes nowadays the standard of care, and should be offered to all patients. Other methods currently under development will potentially bring in the future reliable options for fertility preservation in a wider range of patients, such as those in pre-pubertal age at the time of diagnosis, or with an insufficient sperm count for semen banking. These include testicular sperm extraction (TESE), autologous ovarian tissue transplant, and in vitro maturation of gametes. Novel therapies such as molecular-targeted agents offer a safer toxicity profile regarding fertility, but further research is required to evaluate their impact on the long term, both alone and in combination therapies. Difficulties to access fertility preservation and its costs remain a significant impediment for many patients in need. Warranting access to all sarcoma patients should be a priority in all healthcare professionals involved in their care.